(untitled) (Bangladesh Journal of Botany, 2025)
Deparia chingii, a new species was reported from China. Comparative study was conducted between D. chingii, a new species, and D. patersenii, a related species, using a combination of plant resources, taxonomy, palynology, macrography, micrography, microscopic and submicroscopic structures. The results showed that the leaves of D. chingii were oval rectangular circle, bipinnately lobed, 8-10 pairs of lateral pinnae were close to each other, with short stalks, and the first pair of pinnae on the lower part of the leaves were slightly shortened; the leaves were glabrous on both sides; stipe, rachis and costae were nearly smooth; sori short linear, 4 to 6 pairs per lobe, and the sori were separated from each other when mature, with short pubescent on the dorsal side of the indusium, perispore with auricular ornamentation. The leaves of D. patersenii were ovate-oblanceolate, double pinnation, separated laterally, with 8 to 10 pairs of pinnae; stipe, rachis, costae and both sides of leaf are covered with small scales and nodal pubescence, sori often cover the dorsal lobes when mature, perispore with long columnar or prickly ornamentation. Bangladesh J. Bot. 54(3): 749-753, 2025 (September) Special